2021
DOI: 10.1111/jfb.14872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on collective movement and fission–fusion dynamics in both homogeneous and heterogeneous shoals of a group‐living cyprinid fish species

Abstract: The present study aimed to reveal the effect of fasting (21 days) on collective movement and interaction dynamics in both homogeneous (eight members fed a commercial diet or deprived of food) and heterogeneous (four fed + four starved members) shoals of juvenile qingbo (Spinibarbus sinensis). The authors of this study measured the shoaling behaviour in both a commonly used rectangular open arena with no spatial complexity and a radial arm maze. When measured in the open arena, the starved shoals had a faster s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Goldfish in the digestion groups swam slower than those in either the fasted or control groups, with the two mixed heterogeneous groups swimming at an intermediate level between the rates of those groups. Similarly, previous studies also found that hungry fish swim faster than relatively satiated fish within or among groups (Hansen et al, 2015a(Hansen et al, , 2015bKrause et al, 1998;Wilson et al, 2019;Zheng & Fu, 2021). These findings suggest that the internal nutritional state is one of the key drivers of the general activity levels of individual fish and hence results in individuals with different nutritional states showing specific swimming speed patterns.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Goldfish in the digestion groups swam slower than those in either the fasted or control groups, with the two mixed heterogeneous groups swimming at an intermediate level between the rates of those groups. Similarly, previous studies also found that hungry fish swim faster than relatively satiated fish within or among groups (Hansen et al, 2015a(Hansen et al, , 2015bKrause et al, 1998;Wilson et al, 2019;Zheng & Fu, 2021). These findings suggest that the internal nutritional state is one of the key drivers of the general activity levels of individual fish and hence results in individuals with different nutritional states showing specific swimming speed patterns.…”
Section: Discussionsupporting
confidence: 67%
“…For example, the whole group can break into subgroups according to different individual needs when the whole group is composed of a majority of hungry fish (Hansen et al, 2015a). However, the frequency and duration of decision making of the heterogeneous groups were not different from those of the homogeneous groups in Qingbo (Spinibarbus sinensis) (Zheng & Fu, 2021). Our study did not measure or compare the frequency and duration of group fission-fusion between the heterogeneous and homogeneous groups, but increasing either interindividual or nearest neighbor distance in the fasting group provides more choices for group fission-fusion than in the control or digestion groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological factors like habitat, prey availability and predation strongly control fission-fusion dynamics among schooling fishes [43][44][45]. As in guppies, the analyses of fission-fusion dynamics revealed that in the presence of predator cues, the tendency of individuals to leave the largest subgroup declined significantly [46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the models were defined as follows: where y i,j , is the observed value of a school characteristic of species i at station j in school k, α i is a shape parameter (>0), β i,j is a rate parameter (>0), μ i,j is the expected (mean) value of the school characteristic, x i,j is local population density, a i is a coefficient, b i is a power exponent, and r l is a random effect of date l . Factors other than population density have also been reported to affect schooling behaviour (Borner et al ., 2015; Romenskyy et al ., 2020; Zheng & Fu, 2021), and these factors may cause spatiotemporal autocorrelation in school characteristics. To consider this spatiotemporal autocorrelation, survey date was incorporated into the model as a multiplicative random effect following a normal distribution with mean 1 and standard deviation .…”
Section: Methodsmentioning
confidence: 99%